Myomectomy During Early Pregnancy - Sarsam, Samar D. (AL-Kindy College Medical Journal, 2008)
Myoma is a common benign uterine tumor; therefore it is common in pregnancy. One in ten women will have complications related to myoma in pregnancy. Few treatment options are available during pregnancy, conservative treatment with analgesia, reassurance and supportive therapy is almost always adequate but in carefully selected patients, myomectomy has been performed successfully without jeopardizing pregnancy outcome. The usual indications for surgery during pregnancy include torsion of pedunculated uterine myoma and obstructed labor, surgical intervention during pregnancy is occasionally necessary in uncommon cases of intractable pain. 19 years old lady presented with intractable lower abdominal pain during pregnancy. Ultrasound showed fetus of 18 weeks gestation and ovarian cyst. The pain did not respond to rest and sedation, so emergency exploration laparotomy was done; incarcerated intramural uterine myoma was the cause of the pain, it was enucleated successfully through myomectomy and the pregnancy progressed normally